2009
DOI: 10.1021/jp901628h
|View full text |Cite
|
Sign up to set email alerts
|

How Much Supporting Electrolyte Is Required to Make a Cyclic Voltammetry Experiment Quantitatively “Diffusional”? A Theoretical and Experimental Investigation

Abstract: Theory is presented for cyclic voltammetry at a hemispherical electrode under conditions where the electric field is nonzero and migration is significant to mass transport. The nonlinear set of differential equations formed by combining the Nernst-Planck equation and the Poisson equation are solved numerically, subject to a zero-field approximation at the electrode surface. The effects on the observed voltammetry of the electrode size, scan rate, diffusion coefficient of electroactive and supporting species, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(184 citation statements)
references
References 30 publications
6
178
0
Order By: Relevance
“…As with the data in Figure 2 and Figure S1, these would all, again, be regarded as reasonable concentrations of redox-active species and ratios of electrolyte to redox-active species concentration in conventional cells. 67 However, as with the data in Figure 1 and Table 1, these results highlight the need to use rather extreme electrolyte to redox-active species concentrations in dropletcell kinetic measurements, and the importance of RE and CE placement. In order to diminish the dependence of the voltammetric response on the cell configuration, a larger concentration of supporting electrolyte, 1 M KCl (instead of 0.1 M), was used for the kinetic measurements herein, since this increases the conductivity of the solution by approx.…”
Section: Assessment Of Ohmic Loss Of Potentialsupporting
confidence: 63%
“…As with the data in Figure 2 and Figure S1, these would all, again, be regarded as reasonable concentrations of redox-active species and ratios of electrolyte to redox-active species concentration in conventional cells. 67 However, as with the data in Figure 1 and Table 1, these results highlight the need to use rather extreme electrolyte to redox-active species concentrations in dropletcell kinetic measurements, and the importance of RE and CE placement. In order to diminish the dependence of the voltammetric response on the cell configuration, a larger concentration of supporting electrolyte, 1 M KCl (instead of 0.1 M), was used for the kinetic measurements herein, since this increases the conductivity of the solution by approx.…”
Section: Assessment Of Ohmic Loss Of Potentialsupporting
confidence: 63%
“…The interfacial tension between the kerosene and water phases slightly increases in the presence of salts 39 (typically by a few of mN m −1 ), i.e., the formation of the tip on the droplet surface at a charging electrode is more difficult and the electric charge is transferred from the electrode to the droplet through different surface area. Increased concentration of a supporting electrolyte also reduces the electromigration transport of the electrochemical reactants, 40 which changes the transport rates of these species during the charge/discharge process. It can be concluded that salt addition into the water droplet results in a complex change of system behavior.…”
Section: B Frequency Characteristicsmentioning
confidence: 99%
“…They also solved Poisson's equation, rather than assuming electroneutrality or implementing a displacement-current equation. Dickinson et al 60 subsequently modified the methodology of Streeter and Compton 59 to simulate CV of idealized single-electron transfer reactions at a hemispherical working electrode. Their model also assumed that the electrolyte was weakly to strongly supported and that no mass was transferred from the electrolyte to the electrode.…”
Section: Theorymentioning
confidence: 99%
“…This work builds upon the methodology of Dickinson et al 60 by extending the interfacial reaction model to account for the nucleation, growth, and dissolution of metal deposits, as well as the experimental Coulombic efficiency. The utility of the model is demonstrated by identifying parameter sets that are consistent with experimentally obtained CV data.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation